Analisis Faktor-Faktor yang Mempengaruhi Kunjungan Objek Wisata Air Terjun Colo di Kabupaten Kudus - Hernantyo Budihatmojo; Nugroho SBM (Diponegoro Journal of Economics, 2020)
Kudus is a regency in Central Java Province that has the beauty of natural tourism, that is Colo Waterfall. Colo Waterfall is a tourist attraction that has amount of visitors at the most in Kudus Regency. Despite the fact that it’s an attractive natural tourism, Colo Waterfall yet has many unsolved problems, such as the road access to the location was hampered by the water pipes, then the food stall that has not yet been organized. Purpose of this research is analysing the factors that bring impacts toward the amount of Colo Waterfall tourism visitors. Method of this research is quantitative method, that is multiple linear regression analysis. The Sample of this research is the visitors of Colo Waterfall tourism, and was taken using questionnaire that is shared to 100 respondents. Result of this research shows that travel cost to Colo Waterfall, facilities, and the tourists’ income bring several significant impacts toward the number of the visitors. While another factors, such as group visit and distance does not bring any significant impact toward the amount of the visitors.